Investigation of post-thermal annealing on material properties of Cu–In–Zn–Se thin films. (December 2017) - Güllü, H. H.; Parlak, M.
Abstract: The Cu–In–Zn–Se thin film was synthesized by changing the contribution of In in chalcopyrite CuInSe2 with Zn. The XRD spectra of the films showed the characteristic diffraction peaks in a good agreement with the quaternary Cu–In–Zn–Se compound. They were in the polycrystalline nature without any post-thermal process, and the main orientation was found to be in the (112) direction with tetragonal crystalline structure. With increasing annealing temperature, the peak intensities in preferred orientation became more pronounced and grain sizes were in increasing behavior from 6.0 to 25.0 nm. The samples had almost the same atomic composition of Cu0.5 In0.5 ZnSe2 . However, EDS results of the deposited films indicated that there was Se re-evaporation and/or segregation with the annealing in the structure of the film. According to the optical analysis, the transmittance values of the films increased with the annealing temperature. The absorption coefficient of the films was calculated as around 10 5 cm −1 in the visible region. Moreover, optical band gap values were found to be changing in between 2.12 and 2.28 eV depending on annealing temperature. The temperature-dependent dark- and photo-conductivity measurements were carried out to investigate the electrical characteristics of the films.